A non-linear Ritz method for progressive failure analysis of variable angle tow composite laminates. Issue 5 (4th March 2023) - Campagna, D.; Milazzo, A.; Benedetti, I.; Oliveri, V.
Abstract: A Ritz formulation for non-linear analysis of damage initiation and evolution in variable angle tow composite plates under progressive loading is presented. The model is built on a few key items. It assumes first order shear deformation theory kinematics and non-liner strains in the von Kármán sense. The constitutive relationships are formulated in the framework of continuum damage mechanics at the ply level, so that each laminate layer can experience in-plane damage initiation and evolution, then reflected in material softening and loss of local stiffness. A Ritz polynomial expansion of the primary variables and the minimization of the total potential energy provide the discrete solution equations, which are then solved with an incremental-iterative approach for capturing damage evolution. A few tests have been successfully performed to validate the approach. Eventually, some original results about variable angle tow plates under progressive in-plane compression loads highlight the effect of damage on the post-buckling response.